Reactivación ovárica posparto en vacas cebú Brahman con relación al peso y condición corporal (1997)
ABSTRACT: Eighteen multiparous suckling beef cows (Zebu Brahman) and their calves were selected to determine the influence of body weight (BW) and body condition (BC) in the resumption of postpartum ovarian activity. Data of BC, BW scores and blood sampling, for progesterone determination, were weekly collected since calving until the second estrous postpartum. Cows were divided in two groups G1 (n = 11) between 450 and 480 kg and G2 (n = 7) weighting around 500 and 520 kg. Animals from G1 had a mean of 71 open days while G2 cows had 107 days; 3 cows of this G2 group had 210 open days. The loss weight was higher (p < 0.005) in G2 (35 kg) than in G1 (16 kg) during the experiment period. The 3 cows of G2 previously mentioned lost about 70 kg of the initial weight. All of the animals maintained a constant BC between 3,4 and 3,5. The 18 calves reported daily BW gain of about 600 to 850 g until a mean of 110 kg of weight at the end on the study. The mean serum progesterone concentrations were normal for the 3 groups. The results show that maintenance of BC without dramatical loses of BW give the capacity to the cow to insure good BW gain for calves and to have an early postpartum resumption of ovarian activity.